A Correlation Between Chemotherapy Side Effects And Life Quality Of Breast Cancer Patients At Rsud Dr. M. Yunus In Bengkulu In 2024 - Wardani, Sukma Puja Kusuma; Metasari , Des; Aprianti , Delta (Jurnal Multidisiplin, 2025)
Breast cancer is still a public health problem. Based on data from WHO in the world in 2020 reached 19.3 million cases with deaths of around 10 million people. Globocan (IARC) in 2022, breast cancer patients in Indonesia reached 66,271 cases (16.6%). Breast cancer in Indonesia with the number of deaths is more than 22,598 (9.3%) cases (Angela, 2022). Data from Health Office of Bengkulu Province throughout 2022 the number of breast cancer patients in Bengkulu Province amounted to 345,214 people. Based on data from medical records at RSUD Dr. M. Yunus Bengkulu, the number of breast cancer patients in 2023 was 186 breast cancer patients. This study aims to determine the correlation of chemotherapy side effects with the quality of life of breast cancer patients. The method used was observational analytic research with a cross sectional approach. The method used was observational analytic research with a cross sectional approach. The sampling technique in this study used purposive sampling. This study used consecutive sampling method with 49 respondents.The results of the study of chemotherapy side effects of breast cancer patients showed that most of the side effects of chemotherapy of breast cancer patients were adaptive while the quality of life of breast cancer patients showed that most respondents experienced a good quality of life. This study shows that there is a correlation between chemotherapy side effects and the quality of life of cancer patients with a ρ value of 0.001 which means below <0.05.It is concluded that there is a correlation between chemotherapy side effects and the quality of life of breast cancer patients so it is recommended that families should always motivate and support respondents who undergo chemotherapy to minimize the side effects of chemotherapy with a good quality of life.